Leadership of Nursing Innovation - Prommul, Jirarat; Chullasap, Niran; Ananphitsit, Sirinthanan; Sutthinuan, Atthaporn; Low, Kuwansofia (Princess of Naradhiwas University Journal, 2025)
The purpose of this article was to examine leadership of nursing innovation roles from literature reviews, the current state of the world with its rapidly changing technology, and the competition of the economy, society, and health in both internal and external organizations. These topics are crucial for organization leaders to comprehend and prepare for in order to develop strategies that align with the changes that affect the economy, society, and health in the so-called "VUCA World century." In the century of intense competition, the implementation of changes in the health care system would be essential to the organization's survival and ability to advance. Because science and technology are developing so quickly, the organization is unable to adjust. The trend of vital health change that would he occurred were good health maintenance, risk patient inquiry, illness prevention, and the initial stage of disease healing through the use of technology and innovation in diagnosing and curing patients. Thus, the following were the primary responsibilities of nursing innovation leadership to improve the quality of patient care and improve the efficiency of nursing organization operations: 1) inspiring others; 2) honing leadership skills in nursing innovation; 3) facilitating change; 4) fostering innovation in the workplace culture; 5) integrating new technology with nursing in the digital century; 6) fostering collaboration; and 7) assessing and improving work processing of leadership in nursing innovation. In addition, the leader of nursing care services should be at the forefront of nursing innovation to play a critical role in administering and managing nursing resources that result in efficacy and balance for nursing management to achieve success for customer safety.